Ross on the Dualism of Reality and Validity - SPAAK, Torben (Utopía y Praxis Latinoamericana, 2016)
In this article, I want to consider Alf Ross”™sÂ intriguing 1946 critique of the dualism of reality and validityÂ and the implications of this critique for so-called dual-natureÂ theories of law, such as the theory defended by RobertÂ Alexy. The meaning of this dualism, which Ross considersÂ to be at the foundation of traditional legal thinking, is thatÂ both the very concept of law and certain other fundamentalÂ legal concepts ”“ such as the concept of the sources of lawÂ and the concept of subjective law (which encompassesÂ the concept of a legal right and the concept of a legalÂ duty) ”“ consist of two parts, one factual and empirical andÂ one normative and metaphysical. Ross objects, however,Â that this dualism gives rise to certain very troublesomeÂ antinomies both in the concept of law and in the otherÂ fundamental legal concepts, and that dualists cannot avoidÂ these antinomies by eliminating the concept of validity fromÂ their theories, since doing so would leave the resultingÂ (monist) theory unable to even find its study object, butÂ must instead substitute a non-cognitivist account of claimsÂ of legal validity for the non-naturalist (intuitionist) accountÂ characteristic of such dualism. Â I am, however, going to argue that Ross”™sÂ discussion of the dualism of reality and validity and theÂ ensuing antinomies, although very interesting, is ultimatelyÂ not persuasive, that the solution proposed by Ross toÂ the problem of the antinomies would likely have beenÂ successful if there really had been a problem that needed aÂ solution, and that in any case Ross”™s critique of the dualismÂ of reality and validity does not apply to Robert Alexy”™s dualnatureÂ theory of law.